2008
DOI: 10.2175/193864708788735556
|View full text |Cite
|
Sign up to set email alerts
|

Estimating The Kinetics And Stoichiometry Of Heterotrophic Denitrifying Bacteria With Glycerol As An External Carbon Source

Abstract: Wastewater treatment facilities in the Chesapeake Bay watershed are focusing their attention on nitrogen removal to meet future effluent limitations of about 3-4 mg N/L. External carbon is added during denitrification to facilitate the removal of nitrate. This study investigates the kinetics and stoichiometry of glycerol as an external carbon source for denitrification. Biodiesel-based glycerol acclimated mixed liquor was fed glycerol as an external carbon source in lab scale batch experiments to estimate spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
1
8
1
Order By: Relevance
“…The influent COD:NO3 --N ratio required for glycerol-driven denitrification (NO3 --N to N2 reduction) was thermodynamically 30 determined to be 5.9:1 (see SI). This corresponded well with experimentally-determined operational ratios of 4.2:1 to 5.6:1, 16,20,31 although the lowest reported ratio 16 may not be fully representative as it was determined via ex situ batch assays as opposed to steady-state continuous flow bioreactor or SBR operation. Stoichiometric analysis revealed that influent COD:NO3 --N=2.4:1 (see SI) would provide only enough electrons via COD oxidation to reduce NO3to NO2on a theoretical electron equivalence basis as opposed to full denitrification.…”
Section: Nitrogen Conversion Calculationssupporting
confidence: 79%
See 1 more Smart Citation
“…The influent COD:NO3 --N ratio required for glycerol-driven denitrification (NO3 --N to N2 reduction) was thermodynamically 30 determined to be 5.9:1 (see SI). This corresponded well with experimentally-determined operational ratios of 4.2:1 to 5.6:1, 16,20,31 although the lowest reported ratio 16 may not be fully representative as it was determined via ex situ batch assays as opposed to steady-state continuous flow bioreactor or SBR operation. Stoichiometric analysis revealed that influent COD:NO3 --N=2.4:1 (see SI) would provide only enough electrons via COD oxidation to reduce NO3to NO2on a theoretical electron equivalence basis as opposed to full denitrification.…”
Section: Nitrogen Conversion Calculationssupporting
confidence: 79%
“…Several water resource recovery facilities are switching to glycerol due to the operational and safety risks associated with methanol. 12 Glycerol is similar in cost to methanol and less expensive than ethanol and acetate, [16][17][18] is available as a waste or byproduct, 19,20 and has no known inhibitory effects on the anammox process, unlike methanol. 21 NO2accumulation during glycerol supplementation was also anecdotally observed in full-scale treatment plants resulting in unintentional enrichment of anammox on the produced NO2 -.…”
Section: Introductionmentioning
confidence: 99%
“…Several water resource recovery facilities are switching to glycerol due to the operational and safety risks associated with methanol. 14 Glycerol is similar in cost to methanol and less expensive than ethanol and acetate, 18–20 is available as a waste or byproduct, 21,22 and has no known inhibitory effects on the anammox process, unlike methanol. 23 NO 2 − accumulation during glycerol supplementation was also anecdotally observed in full-scale treatment plants resulting in unintentional enrichment of anammox on the produced NO 2 − .…”
Section: Introductionmentioning
confidence: 99%
“…Similar values were obtained with dairy effluent, glycerin and meat processing wastewater. Some other studies, for instance, with glycerol, fusel oil, brewery effluent, and wine distillery effluent revealed values exceeding 13 mg N/(g VSSh) (Monteith et al, 1980;Bernet et al, 1996;Hinojosa et al, 2008;Kampas et al, 2009).…”
Section: Introductionmentioning
confidence: 92%